Thickness of Polyelectrolyte Layers of Separately Confined Bacteria Alters Key Physiological Parameters on a Single Cell Level - Rybkin, Iaroslav; Gorin, Dmitry; Sukhorukov, Gleb; Lapanje, Aleš (Frontiers in Bioengineering and Biotechnology, 2019)
Confinement of bacterial cells in matrix or capsules is an integral part of many biotechnological applications. Here, it is adopted the well-known layer-by-layer method of deposition of a few nanometer thick polyelectrolyte layers to confine separated bacterial cells in permeable and physically durable shells. Due to the physical properties of such a confinement, here it is found that this method enables investigation of effects of physical barrier against the mass gain and cell division. Using the method of time-lapse confocal microscopy, it is observed a prolonged lag phase, dependent on the number of polyelectrolyte layers. In the confinement, both the GFP fluorescent signal from the leaking T7 promoter and cell size, were increased by more than five and two times, respectively. This creates paradigm shift that enables using mechanical entrapment for control of bacterial cell physiology which opens possibilities of controlling the division rate as well as gene expression. These effects can be attributed to the perturbation of the sensing of the cell size, which results in disproportional synthesis of cell envelope against the intracellular material and compels cells to grow rapidly. In addition, the charged surface of cells enabled longer intercellular physical interaction resulting in spherically shaped microcolonies.